Pengaruh Penerapan E-Filing, Pemahaman Perpajakan, Dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Di Kantor Pelayanan Pajak Pratama Surabaya Mulyorejo - Syafii Syafii; Tatok Kushartanto (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
Tax revenue is one of the sources of state revenue managed to finance various sectors of state spending needs. This research was conducted with the aim of determining the effect of implementing the e-filing system, the level of understanding of taxation and taxpayer awareness of taxpayer compliance with KKP Pratama Surabaya Mulyorejo. The data collection technique in this study used questionnaire dissemination and the sampling technique used was purposive sampling. Where the data will be analyzed using quantitative analysis methods with multiple linear regression tests. The results showed that the implementation of the e-filing system affects individual taxpayer compliance, the level of taxation understanding does not affect individual taxpayer compliance, taxpayer awareness affects individual taxpayer compliance, and the application of the e-filing system , the level of tax understanding, and taxpayer awareness simultaneously affect taxpayer compliance with KPP Pratama Surabaya Mulyorejo.